Is rainfall seasonality important for reproductve strategies in viviparous neotropical pit vipers? A case study with Bothrops leucurus from the Brazilian Atlantc Forest - Barros, Verônica Alberto [UNESP]; Rojas, Claudio Augusto; Almeida-Santos, Selma Maria [UNESP] (My University, 2014)
Two populatons of the Neotropical lancehead Bothrops leucurus were studied in two locatons in Brazil (Espírito Santo, ES, and Bahia, BA) with different rainfall seasonality paterns. The timing of reproducton was very similar in both populatons, with the mating season occurring in autumn (when spermatozoa were found in uteri) and births occurring in summer. In males, spermatogenesis peaked in autumn, with evidence for increased secretory actvity in the epithelium of the ductus deferens during the mating season in both populatons. Our results indicate that phylogenetc inerta plays a major role in determining the timing of reproductve events in B. leucurus. However, snout-vent length (SVL) and clutch size were l'arger in individuals from BA than ES, which may be a result of differences in rainfall seasonality or other proximate factors (e.g., differential prey availability).
Keywords: Clutch size; Environmental conditons; Long-term sperm storage; Phylogenetc inerta; Reproductve cycles; Spermatogenesis